Закон подлости: [роман] / Андрей Таманцев - Таманцев Андрей (Солдаты удачи, 2003)
Экземпляры: ф.4 (20150420) / Инвентарный номер: 51561 / Цена: 20. 00. / Сис.шифр: Р2 / Авт.знак: Т 17 / ГРНТИ: 17.82.31 / ББК: 84(2РОс=Рус)6